PEMANFAATAN MEDIA PLICKERS SEBAGAI ASESMEN SUMATIF UNTUK MENGURANGI BUDAYA MENYONTEK SISWA PADA IPAS MATERI SISTEM PERNAPASAN MANUSIA KELAS V UPT SDN 060817 MEDAN - Marcella Andhyama; Fitrah Dwi, Dara; Rapita Silalahi, Beta; Husna, M. Faisal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to utilize Plickers media as a summative assessment to reduce theculture of cheating among fifth-grade students of UPT SDN 060817 Medan on the Human Respiratory System material in the subject of Science. This study is a quantitative study with a Pre-Experimental Design research design in the form of One-Group Pretest-Posttest Design involving 27 fifth-grade students as research subjects. Data collection was carried out using knowledge tests and cheating behavior observation sheets that have been validated by experts. Data analysis used descriptive statistics including mean, standard deviation, and frequency distribution. The results of the study showed a significant increase in student learning outcomes, with the average score increasing from 46.49 (pretest) to 90.81 (post-test), an increase of 44.32 points. In terms of cheating behavior, the average score dropped drastically from 77.62 (pretest) to 36.75 (post-test), a decrease of 40.87 points. The use of Plickers has proven to be very effective in reducing the culture of cheating because the QR card individualization system makes cheating almost impossible. It can be concluded that the use of Plickers media as a summative assessment is effective in reducing the culture of cheating and improving student learning outcomes.